Organizing Matters: The Case of Medical Rehabilitation. (September 2019) - Baker, Diane F.
Students frequently struggle to understand the differences among various types of organizational structures and how these differences affect organizational processes and outcomes. In the exercise described in this article, students are given a list of jobs from a medical rehabilitation center and asked to create an organizational chart. Students are thereby encouraged to consider how various jobs relate to each other and to customers (in this case, the patients). Students evaluate the charts that they and their peers have created to determine how well each structure supports coordination, collaboration, customer responsiveness and job satisfaction. The exercise is appropriate for undergraduate, graduate, and professional learners.